A bibliometric analysis of the anxiety disorder topics in 2023 - M. Fahli Zatrahadi; Miftahuddin Miftahuddin; Ifdil Ifdil; Istiqomah Istiqomah (KONSELOR, 2023)
This research provides a bibliometric analysis of anxiety disorder studies in 2023, employing a qualitative approach to examine trends and developments in this field. The study analyzes 988 documents, utilizing OpenRefine, Vosviewer, and Rstudio for in-depth data analysis. The primary objective is to understand the current landscape of anxiety disorder research and identify key themes and contributors. The findings reveal that anxiety disorder remains a significant and topical subject in contemporary research, with a notable concentration of studies originating from the United States. This geographic focus underscores the country's leading role in advancing research in this area. A key figure in this field is identified as Wang Y., who has made substantial contributions through frequent publications. The study also highlights emerging areas of interest within anxiety disorder research. These include specific focus on teenagers and women, indicating a growing awareness of demographic-specific anxiety issues. Additionally, the research points to an increasing interest in exploring the nuances of gender in relation to anxiety disorders. Another critical aspect underlined by the study is the broader theme of mental stress, which remains a pertinent issue in understanding and addressing anxiety disorders. Overall, this research not only maps the current state of anxiety disorder studies but also indicates key directions for future research, emphasizing the importance of demographic-specific and thematic explorations in this field. The insights gained from this study are valuable for researchers, clinicians, and policymakers, providing a foundational understanding of the evolving landscape of anxiety disorder research in 2023.